Endorsement Korean Wave : Fanatisme Generasi Muda Muslim Terhadap Produk Mie Lemonilo Di Kota Makassar - Nabila Ramadani; Sirajuddin; Putra, Trisno Wardy (Universitas Islam Negeri Alauddin Makassar, 2025)
ABSTRACT- This study presents two research questions, namely: first, What are the factors that influence the level of fanaticism towards Lemonilo Noodles? Second, What is the Islamic jurisprudence's view on Korean Wave endorsements in increasing Lemonilo Noodle sales? The phenomenological research approach is combined with qualitative research methodology in this study. Primary data or data obtained directly from primary sources is the data source used in this study. Information collection was carried out using interview and documentation strategies. The results of this study conclude that Lemonilo has succeeded in building a fanatical attitude among the young Muslim generation in Makassar by using Korean artist endorsements that are widely liked by the young generation in Indonesia. This phenomenon provides valuable lessons on how a product can build consumer loyalty, especially Muslim consumers, without ignoring sharia aspects or contemporary trends. The implications of this study are: (1) this study enriches the study of halal product marketing that successfully integrates Korean Wave endorsement strategies while still paying attention to Islamic values. (2) Lemonilo's success in building Muslim consumer loyalty without sacrificing religious aspects can be a reference model for other companies targeting similar markets. (3) demonstrates the ability of the young Muslim generation in Makassar to adopt modern trends while maintaining Islamic values. Keywords: Endorsement, Korean Wave, K-Pop, Fanaticism, Mie Lemonilo